Robots and Labor Regulation: A Cross-Country/Cross-Industry Analysis - Silvio Traverso; Massimiliano Vatiero; Enrico Zaninotto (Global Labor Organization (GLO), 2021)
This work discusses and empirically investigates the relationship between labor regulation and robotization. In particular, the empirical analysis focuses on the relationship between the discipline of workers' dismissal and the adoption of indus- trial robots in nineteen Western countries over the 20062016 period. We find that high levels of statutory employment protection have been negatively associated with robot adoption, suggesting that labor-friendly national legislations, by increasing adjustment costs (such as firing costs), and thus making investment riskier, provide less favorable environments for firms to invest in industrial robots. We also find, however, that the correlation is positively mediated by the sectoral levels of capital intensity, a hint that firms do resort to industrial robots as potential substitutes for workers to reduce employees' bargaining power and to limit their hold-up opportu- nities, which tend to be larger in sectors characterized by high levels of operating leverage.
Keywords: K31; O31; 330; Robot adoption; Labor regulation; Hold-up